2014
DOI: 10.1016/j.juro.2013.10.096
|View full text |Cite
|
Sign up to set email alerts
|

Timing, Incidence and Risk Factors for Venous Thromboembolism in Patients Undergoing Radical Cystectomy for Malignancy: A Case for Extended Duration Pharmacological Prophylaxis

Abstract: More than half of all venous thromboembolisms (55%) in patients undergoing radical cystectomy for malignancy occurred after discharge home and the mean time to venous thromboembolism diagnosis was 15.2 days postoperatively. It is reasonable to consider extended duration pharmacological prophylaxis (4 weeks) in this high risk surgical population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
52
3
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(64 citation statements)
references
References 15 publications
5
52
3
4
Order By: Relevance
“…An incidence of 1.8% recorded in this study is comparable with other contemporary series which report VTE rates varied between 0.4 and 5.5% in major urologic oncology surgery [2-5]. We also found that radical cystectomy confers a greater risk of VTE compared to radical cystectomy, again in keeping with published data [6][7][8][9][10][11][12][13]. The probable reason for this is the fact that patients undergoing radical cystectomy have greater risk factors for VTE compared to those undergoing radical prostatectomy.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…An incidence of 1.8% recorded in this study is comparable with other contemporary series which report VTE rates varied between 0.4 and 5.5% in major urologic oncology surgery [2-5]. We also found that radical cystectomy confers a greater risk of VTE compared to radical cystectomy, again in keeping with published data [6][7][8][9][10][11][12][13]. The probable reason for this is the fact that patients undergoing radical cystectomy have greater risk factors for VTE compared to those undergoing radical prostatectomy.…”
Section: Discussionsupporting
confidence: 91%
“…Tyritzis et al reported that LND was associated with six to eightfold greater risk of VTE in patients undergoing radical prostatectomy [12]. Similarly VanDlac et al found that the length of operation during radical cystectomy was one of the risk factors associated with VTE [13]. Furthermore, Tollefson et al reported blood type, pelvic lymph node dissection and blood transfusion were significant risk factors for symptomatic VTE [14].…”
Section: Discussionmentioning
confidence: 99%
“…Potretzke et al detected symptomatic VTE in 8.3% of patients after radical oncological cystectomy [186]. VanDlac and Rosario estimated in two independent trials that the risk for symptomatic VTE in patients after radical cystectomy amounts to 6% [187,189]. Based on treatment results of 1581 patients after radical cystectomy performed due to urinary bladder cancer, James reported that VTE occurred in 10% of the cases within 90 days after surgery [189].…”
Section: Venous Thromboembolism Prophylaxis In Cancer Patientsmentioning
confidence: 99%
“…Leibovitch et al concluded in their study that 7 of 9 cases of DVT diagnosed after radical retropubic prostatectomy occurred after discharge [192]. VanDlac et al reported that in a group of 1,307 patients after radical cystectomy, 55% of VTE events were diagnosed after discharge [252]. The study performed by Kukreja et al, is one of the few works on appropriate antithrombotic prophylaxis duration in urology [253].…”
Section: Venous Thromboembolism Prophylaxis In Cancer Patientsmentioning
confidence: 99%
“…Rates of DVT and PE in the perioperative period of radical cystectomy range from 0.6% to 4.7% and 0.6% to 2.0%, respectively [85][86][87][88] . While the risk factors for VTE are common to the bladder cancer patient, it has also been established that surgery itself is an independent risk factor for developing VTE 85 .…”
Section: Extended Venous Thromboembolism Prophylaxismentioning
confidence: 99%